Satisfaction with Social Roles and Physical Function in Immune-mediated Inflammatory Diseases: A Cross-Sectional Study - Spagnuolo, Rocco; Iaquinta, Francesco S.; Mauro, Daniele; Pantano, Ilenia; Dastoli, Stefano; Naty, Saverio; Cosco, Cristina; Mancina, Rosellina Margherita; Iacono, Daniela; Gaggiano, Emanuela; Ruggiero, Annarita; Nisticò, Steven Paul; et al. (Reviews on Recent Clinical Trials, 2022)
Background: Although mood disorders have been well characterized by immunemediated inflammatory diseases, physical function and satisfaction with social roles have not yet been defined as independent domains. Objective: The study aims to assess satisfaction with social roles and physical function alterations in a population with immune-mediated inflammatory diseases and identify associated characteristics. Methods: Physical function and social role satisfaction were evaluated through the Patientreported Outcomes Measurement System. Besides comparison between groups, univariate and multivariable logistic regression analyses were performed to identify independent predictors. Results: Two hundred sixty-five patients with immune-mediated inflammatory diseases and 206 controls were recruited. Compared to controls, patients with inflammatory bowel diseases had impaired physical function (p<0.001), while patients with inflammatory arthritis reported impairment in both domains (p<0.001, each). In the univariate logistic regression, gender, high school educational level, physical activity, and occupation were positively associated with physical function and social role satisfaction (p<0.001; p=0.001; p<0.001; p=0.001 and p<0.001; p=0.012; p=0.008; p=0.004, respectively). Active disease and steroids were inversely associated with physical function and social roles satisfaction (p=0.033; p=0.022 and p=0.002; p=0.038, respectively). Further associations were found between age and physical function (p=0.002) and biological treatment and ESR with social roles satisfaction (p<0.001; p=0.043; respectively). In the multivariable regression, gender was found to be associated with physical function (p<0.001) and social roles satisfaction (p=0.003). Negatively associated factors were biological treatment for satisfaction with social roles (p<0.001) and steroids for physical function (p=0.021), and social roles satisfaction (p=0.018). Conclusion: Immune-mediated inflammatory diseases determine alterations in physical function and social life satisfaction. Gender and treatment are independently associated factors. Patientreported outcomes should be considered in clinical management to define patients’ real needs.
Keywords: Immune-mediated inflammatory diseases